Sex-Related Effects of Adrenergic Drugs on Conditioned Pain Modulation: A Randomized Controlled Cross-Over Double-Blind Trial - Marie-Philippe Harvey; Marie-Chantal Dubois; Philippe Chalaye; Yanick Sansoucy; Serge Marchand (Pain Research and Management)
Objective. Endogenous pain inhibition can be investigated using conditioned pain modulation (CPM). CPM efficacy has been reported to be influenced by various factors, such as gender and cardiovascular (autonomic) activity. The aim of this study is to describe the effect of pharmacological manipulations of autonomic activity on CPM efficacy. Methods. Thirty healthy participants were enrolled to assess CPM efficacy in 4 experimental sessions. The first session consisted of the determination of baseline CPM effectiveness. The three following sessions were performed in a randomized order and consisted of the injection of (1) esmolol, (2) ephedrine, or (3) placebo, before the conditioning stimulus. Pain intensity induced by using a contact heat stimulation thermode was compared before and after a cold-pressure conditioning stimulus to evaluate CPM effectiveness. Results. Our results show that inhibiting sympathetic nervous activity with esmolol did not have a significant effect on CPM. Conversely, enhancing sympathetic nervous activity with ephedrine increased CPM effectiveness in healthy women but decreased it in men. Conclusions. Increasing sympathetic activity with adrenergic agonists, such as ephedrine, could improve CPM effectiveness in women. It will be interesting to verify if the same results are present in patients suffering from chronic pain and if adrenergic agonists could have better therapeutic effects in women showing reduced CPM effectiveness.